PUNJAB CUISINE: RICHNESS OF KHAN PAN (International Journal of Food and Nutritional Sciences, 2022)
Punjabi cuisine, an emblem of India’s rich culinary heritage, is celebrated for its robust flavors, rich textures, and diverse ingredients. This paper explores the historical development, traditional cooking methods, and cultural significance of Punjabi food. It investigates signature dishes like Butter Chicken, Sarson da Saag with Makki di Roti, and Chole Bhature, examining their preparation techniques, regional variations, and the role of staple ingredients such as mustard oil, dairy products, and spices.Historical influences, including Persian, Mughal, and Central Asian culinary practices, have shaped Punjabi cuisine, contributing to its distinctive flavor profiles and cooking techniques. The paper also delves into the social and cultural contexts of Punjabi food, emphasizing its role in communal dining and hospitality. Festive foods and ritualistic dishes reflect the deep-rooted cultural and religious values of the region.the impact of globalization on Punjabi cuisine is analyzed, highlighting the emergence of fusion dishes and the adaptation of traditional practices to modern culinary trends. The study addresses health aspects, comparing traditional and contemporary dietary practices and their implications for nutrition and wellness.By examining these elements, the paper aims to provide a comprehensive understanding of how Punjabi cuisine embodies regional identity, cultural continuity, and adaptability in a globalized world. The research underscores the significance of preserving culinary traditions while embracing innovation and change.